The effect of creatine on treadmill running with high-intensity intervals - Biwer, C. J.; Jensen, R. L.; Schmidt, W. D.; Watts, P. B. (The Journal of Strength and Conditioning Research, 2003)
To determine whether creatine monohydrate supplementation would improve performance during a submaximal treadmill run interspersed with high-intensity intervals, 15 college soccer players (8 women, 7 men) received either creatine or a maltodextrin placebo at 0.3 g·kg body mass per day for 6 days. The speed of the treadmill was constant at 160.8 m·min, and every 2 minutes the grade was elevated to 15%. Each hill segment was 1 minute long. At the end of the 20-minute protocol, the treadmill was again elevated to 15% and held there until volitional exhaustion occurred. There was a significant treatment effect of creatine supplementation on body mass (p < 0.05) in the men; however, no significant differences were observed in the women (p > 0.05). There were no treatment effects (p > 0.05) on time to exhaustion, ratings of perceived exertion, or blood lactate concentration. There was a tendency for blood lactate levels to be lower after short-term creatine supplementation in the women, but this was not statistically significant. Based on these results, it appears that creatine supplementation does not improve performance in submaximal running interspersed with high-intensity intervals.